Icelanders’ perspectives on security and foreign affair - Ómarsdóttir, Silja Bára (Stjórnsýslustofnun, 2018)
Icelanders’ views on security and foreign affairs since the end of the Cold War are an understudied issue. This article presents the findings of a large scale survey on the position and ideas about foreign affairs and security. The survey was conducted by the Social Science Research Institute of the University of Iceland in November and December 2016. The results of the survey are placed in the context of developments in security studies, with an emphasis on security sectors, ontological security, and securitization. The main findings are that the Icelandic public believes that its security is most threatened by economic and financial instability, as well as natural hazards, but thinks there is a very limited chance of military conflict or terrorist attacks directly affecting the country. These findings are incongruent with the main emphases of Icelandic authorities, as they appear in security policy and political discourse. It is therefore important that the authorities understand how to engage with the public about the criteria upon which risk assessments and security policies are based. Afstaða Íslendinga til öryggismála hefur lítið verið rannsökuð frá því í lok kalda stríðsins. Í þessari grein eru kynntar niðurstöður könnunar um afstöðu til og hugmyndir um utanríkis- og öryggismál, en Félagsvísindastofnun HÍ vann könnunina í nóvember og desember 2016. Niðurstöður könnunarinnar eru settar í samhengi við þróun í öryggisfræðum, þá sérstaklega öryggisgeira (e. security sectors) verufræðilegt öryggi (e. ontological security) og öryggisvæðingu (e. securitization). Helstu niðurstöður eru að almenningur á Íslandi telur öryggi sínu helst stafa ógn af efnahagslegum og fjárhagslegum óstöðugleika og náttúruhamförum, en telur litlar líkur á því að hernaðarátök eða hryðjuverkaárásir snerti landið beint. Þessar niðurstöður eru í takmörkuðu samræmi við helstu áherslur stjórnvalda í öryggismálum og því mikilvægt að stjórnvöld átti sig á því hvernig hægt er að tryggja það að almenningur sé meðvitaður um þær forsendur sem ...